Effects of hot air and microwave drying on kinetic rate and mechanical property of oil palm veneer - Puttipong Lekachaiworakul; Panya Dangvilailux; Chaiwat Rattanamechaiskul (My University, 2017)
This research was studied, the hot air and microwave drying of Oil Palm Veneer (OPV). The oil palm trees at 27 years of age were collected from a plantation in Chumphon. They were processed into a dimension of 80 x 150, 1 mm (thickness) and initial moisture 345 % (db.). The chamber of oven is size of 500 x 1,000 x 1,000 mm3. It had an electrical heater at maximum power output of 5,000 watts, air speed of 2.1 m/s and the microwave power level of 1,000-4,000 watts. The final moisture content reached 10±2% (db). The results were showed that while OPV drying with the hot air condition used temperature about 50, 70 and 90 °C reached the target value within 70, 32 and 16 min respectively, the microwave condition used to power about 2,000 and 3,000 watts reached the target value within 62 and 34 min, combined condition used hot air 50 °C with microwave power level 2,000 and 3,000 watts, hot air 70 °C with microwave power level at 2,000 and 3,000 watts and hot air 90 °C with microwave power level 2,000 and 3,000 watts reached the target value within 24, 20, 14, 10, 10 and 8 min respectively. Moreover, drying with hot air and microwave on high power revealed the tensile stress and shear properties increased. However, the hot air at 70, 90 °C combines with the microwave power level 2,000 watts were better than mechanical properties of hot air at 70, 90 °C combines with microwave power level 3,000 watts. The results showed the drying of hot air at 90 °C combine with the microwave power level at 2,000 watts, mechanical properties of OPV dried tensile stress at 1.9447 MPa, shear stress 19.0286 MPa, which used of energy 39 kWh, its surface was cracked burns. Therefore, the drying hot air only conditions at 90 °C can be recommended for mechanical properties, tensile stress 1.8229 MPa, shear stress 18.4472 MPa, used of energy 21 kWh, which was OPV suitable and cost optimality.
Keywords: Air dryer; Wood Treatment and Properties